Management of Severe Bleeding in Patients Treated with Direct Oral Anticoagulants: An Observational Registry Analysis. (July 2017) - Albaladejo, Pierre; Samama, Charles-Marc; Sié, Pierre; Kauffmann, Sophie; Mémier, Vincent; Suchon, Pierre; Viallon, Alain; David, Jean Stéphane; Gruel, Yves; Bellamy, Lorenn; de Maistre, Emmanuel; Romegoux, Pauline; et al.
Abstract : Background: The use of prothrombin complex concentrates and the role of plasma concentration of anticoagulants in the management of bleeding in patients treated with direct oral anticoagulants are still debated. Our aim was to describe management strategies and outcomes of severe bleeding events in patients treated with direct oral anticoagulants. Methods: We performed a prospective cohort study of 732 patients treated with dabigatran, rivaroxaban, or apixaban hospitalized for severe bleeding, included prospectively in the registry from June 2013 to November 2015. Results: Bleeding was gastrointestinal or intracranial in 37% (212 of 732) and 24% (141 of 732) of the cases, respectively. Creatinine clearance was lower than 60 ml/min in 61% (449 of 732) of the cases. The plasma concentration of direct oral anticoagulants was determined in 62% (452 of 732) of the cases and was lower than 50 ng/ml or higher than 400 ng/ml in 9.2% (41 of 452) and in 6.6% (30 of 452) of the cases, respectively. Activated or nonactivated prothrombin complex concentrates were administered in 38% of the cases (281 of 732). Mortality by day 30 was 14% (95% CI, 11 to 16). Conclusions: Management of severe bleeding in patients treated with direct oral anticoagulants appears to be complex. The use of prothrombin complex concentrates differs depending on bleeding sites and direct oral anticoagulant plasma concentrations. Mortality differs according to bleeding sites and was similar to previous estimates. Abstract : In a prospective cohort registry study of 732 patients treated with direct oral anticoagulants and hospitalized for severe bleeding, bleeding sites were gastrointestinal in 37% and intracranial in 24% of the cases. Activated or nonactivated prothrombin complex concentrates were administered in 38% of the cases with a day 30 mortality of 13.5% and varied according to bleeding sites but was similar to previous reports. Our report provides a detailed assessment of direct oral anticoagulant-treated patients managed in clinical settings.